From supramolecular organic cages to porous covalent organic frameworks for enhancing iodine adsorption capability by fully exposed nitrogen-rich sites - Cheng, Ke (2023)
In order to overcome the limitations of supramolecular organic cages for their incomplete accessibility of active sites in the solid state and uneasy recyclability in liquid solution, herein a nitrogen-rich organic cage is rationally linked into framework systems and four isoreticular covalent organic frameworks (COFs), that is, Cage-TFB-COF, Cage-NTBA-COF, Cage-TFPB-COF, and Cage-TFPT-COF, are successfully synthesized. Structure determination reveals that they are all high-quality crystalline materials derived from the eclipsed packing of related isoreticular two-dimensional frameworks. Since the nitrogen-rich sites usually have a high affinity toward iodine species, iodine adsorption investigations are carried out and the results show that all of them display an enhancement in iodine adsorption capacities. Especially, Cage-NTBA-COF exhibits an iodine adsorption capacity of 304 wt%, 14-fold higher than the solid sample packed from the cage itself. The strong interactions between the nitrogen-rich sites and the adsorbed iodine species are revealed by spectral analyses. This work demonstrates that, utilizing the reticular chemistry strategy to extend the close-packed supramolecular organic cages into crystalline porous framework solids, their inherent properties can be greatly exploited for targeted applications.